MBA - Pro One Software (Firm) (Las Cruces, N.M. : Pro One Software)
"An essential career development resource for anyone seeking advancement to front-line, senior or executive management"
Marketing -- Finance -- Business Statistics -- Economics -- Financial Accounting -- Additional Learning Resources.
Title from container.
System requirements: IBM compatible PC (486 DX2 or greater); 8 MB of RAM (12 MB recommended); Windows 3.1 or higher; 2X CD-ROM drive; video display of 256 colors; (640 X 480 resolution); 16-bit soundcard.
Keywords: Marketing; Finance; Business Statistics; Economics; Financial accounting; Computer software; CD-ROMs.